2002
DOI: 10.1093/jnci/94.12.936
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Glutathione S-Transferase P1, T1, and M1 Genetic Polymorphism and Survival of Patients With Metastatic Colorectal Cancer

Abstract: The GSTP1 Ile(105)Val polymorphism is associated in a dose-dependent fashion with increased survival of patients with advanced colorectal cancer receiving 5-FU/oxaliplatin chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
186
3
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(202 citation statements)
references
References 27 publications
6
186
3
7
Order By: Relevance
“…The explanation of polymorphisms in GSTP1 gene on the efficacy of detoxifying cytotoxins generated by chemotherapeutics might be impairment of the GSTP1 capacity caused by the AgG substitution, patients with the Val variant allele may be less capable of detoxifying oxaliplatin compared to patients with wide-type allele. Our study indicated GSTP1 Val/Val has forable overall survival, which is agreement with previous reports in various cancers, including breast, colorectal (Stoehlmacher et al, 2002;Kweekel et al, 2008). ERCC1 and ERCC2 are potentially relevant to cancer because of their involvement in the process of nucleotide expcision repair (NER) (Goode et al, 2002), and the NER acts a role in repairmen of DNA damaged by environment and UV damage, and the polymorphisms in the two DNA repared genes may change the function of NER in repairing DNA damage by chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…The explanation of polymorphisms in GSTP1 gene on the efficacy of detoxifying cytotoxins generated by chemotherapeutics might be impairment of the GSTP1 capacity caused by the AgG substitution, patients with the Val variant allele may be less capable of detoxifying oxaliplatin compared to patients with wide-type allele. Our study indicated GSTP1 Val/Val has forable overall survival, which is agreement with previous reports in various cancers, including breast, colorectal (Stoehlmacher et al, 2002;Kweekel et al, 2008). ERCC1 and ERCC2 are potentially relevant to cancer because of their involvement in the process of nucleotide expcision repair (NER) (Goode et al, 2002), and the NER acts a role in repairmen of DNA damaged by environment and UV damage, and the polymorphisms in the two DNA repared genes may change the function of NER in repairing DNA damage by chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have confirmed there was association between GSTP1 105 IIe allele and platinum-containing chemotherapy (Howells et al, 2004;Lee et al, 2005). However, some other studies have reported opposite associations or no relationship between the GSTP1 IIe105 Val polymorphism and survival (Stoehlmacher et al, 2002;Beeghly et al, 2006;Marsh et al, 2007;Nagle et al, 2007). These contradictions may be partly attributable to differences in the chemical structures and reaction kinetics of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Both GSTT1-and GSTM1-null were reported a higher risk for ovarian cancer (Howells et al, 2004) and gastric cancer (Ott et al, 2008). However, previous studies showed the inactive genotypes GSTT1-null and GSTM1-null were associated with improved survival in breast cancer, breast cancer, colorectal cancer and advanced gastric cancer prognosis (Ambrosone et al, 2001;Stoehlmacher et al, 2002;Goekkurt et al, 2006). The contradiction results may be due to the different risk factors of gastric cancer in different ethnicities.…”
Section: Discussionmentioning
confidence: 99%